Aromatic and Medicinal Plants - Back to Nature 2017
DOI: 10.5772/66618
|View full text |Cite
|
Sign up to set email alerts
|

From Medicinal Plant Raw Material to Herbal Remedies

Abstract: The use of medicinal plants is old as the existence of mankind. According to World Health Organization (WHO) data, about 80% of world population are using products based on medicinal herbs. Phytotherapy is based on the use of herbal drugs and medicinal products for the purpose of prevention and treatment. Rational phytotherapy is a modern concept of herbal medicines using, which are made of standardized herbal extracts. The quality of each final product is guaranteed by the use of raw materials of a standard q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…The eluent was composed of phosphate buffer (pH 8.8) and 30% acetonitrile, with a flow rate of 1 mL/min, and a chromatography time of 30 min. The collection of individual substances was carried out automatically using a fraction collector [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eluent was composed of phosphate buffer (pH 8.8) and 30% acetonitrile, with a flow rate of 1 mL/min, and a chromatography time of 30 min. The collection of individual substances was carried out automatically using a fraction collector [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Olsen [2] and Djordjevic [3] estimated that 70% to 80% of the people in developing countries use raw medicinal plants to meet their primary health care needs. This high percentage is attributed to several factors including limited accessibility, availability, and affordability of modern medicines [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In primary health care around the world, medicinal plants are demonstrating great importance. Studies reported by the World Health Organization (WHO), have shown that around 80 % of the world's population is using herbs to prevent or treat a wide range of diseases (Arslan and Bektas, 2018;Djordjevic, 2017;Yusuf and Mericli, 2016). Hawthorn has been well-known as an extremely important and valued medicinal plant.…”
Section: History and Traditional Usementioning
confidence: 99%